Palm oleic acid based alkyds: effect of the fatty acid content on the polyesterification kinetics - Ataei, S.; Yahya, Rosiyah; Gan, S.N. (Springer, 2011)
The kinetic behavior of polyesterification of the alkyd resins synthesized using glycerol and phthalic anhydride modified with oleic acid from the palm oil at temperatures between 120 and 240 Â°C was studied. Three alkyds having oleic acid contents of 28, 40, and 65 were prepared by employing fatty acid method. The extent of the polyesterification reaction and average degree of polymerization were monitored by determining the acid number of the aliquot of the reaction mixture at various intervals of time and by measuring the volume of water evolved. Kinetic studies revealed that initial reaction rates followed a second-order kinetics up to certain limit and thereafter deviations were observed. The extent of reaction varied from 77.4 to 86.3 before deviation for all the three samples and exhibited a considerable degree of conversion. The second-order rate constants calculated from the linear part were found to be of the order of 10 -5 g (mg KOH) -1 min -1. Molecular weight of the alkyd samples was determined by GPC; number average molecular weight of the alkyds ranged from 980 to 2,070.